Guidelines on the radical management of patients with lung cancer. (12th October 2010) - Lim, Eric; Baldwin, David; Beckles, Michael; Duffy, John; Entwisle, James; Faivre-Finn, Corinne; Kerr, Keith; Macfie, Alistair; McGuigan, Jim; Padley, Simon; Popat, Sanjay; Screaton, Nicholas; et al.
Abstract : A joint initiative by the British Thoracic Society and the Society for Cardiothoracic Surgery in Great Britain and Ireland was undertaken to update the 2001 guidelines for the selection and assessment of patients with lung cancer who can potentially be managed by radical treatment.